PEMBINAAN BADAN KETAHANAN PANGAN DAN PELAKSANA PENYULUH PERTANIAN KOTA PEKANBARU TERHADAP OPTIMALISASI USAHA KELOMPOK TANI DI KECAMATAN RUMBAI TAHUN 2014 - Julian Arwansyah; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Farmers are key to the fulfillment of human needs for food. The more optimal farmers' efforts in improving farming the better the nutritional needs of people in Indonesia. Therefore, development of farmers is one of the important agenda of the government to meet national food needs, so that agricultural development can run with the objective to be achieved. In the city of Pekanbaru District of Rumbai is one of the agricultural area. Rumbai districts is that the District has the largest farmer group, so the coaching group in the District Rumbai must be considered. This study aims to investigate the implementation of tasks Executing Agency for Food Security and Agricultural Extension Pekanbaru city in the implementation of the District farmer group formation Rumbai 2014. And looking at the obstacles faced UPTB-PP as the implementation of the field coaching duties in the optimization of farming in the District Rumbai 2014. The method used in this study using a qualitative approach. The type and source of the data obtained from this study collected primary data sourced from informants research and secondary data obtained from books and journals related to the research. On data collection in this study conducted by direct observation of the research object and in-depth interviews with research informants such as Head UPTB-PP Pesisir subdistrict Tassel, member UPTB and farmers who are members of the board and members of farmers in the district Rumbai. Based on these findings the authors find the implementation of the field coaching duties UPTB-PP to the optimization of farmers' groups in the District Rumbai Tahun2014've done coaching. the coaching process is done by giving guidance and training and periodic supervision. Constraints experienced UPTB-PP in fostering farmer groups because of limited ability and understanding of the farmers in the district Rumbai in implementing the guidance material provided, plus the lack of participation of farmers in the following activities provided UPTB-PP. Keywords: Development, Agricultural Development, Objective